FISHERY AND BIOLOGY OF THE OIL-SARDINE, SARDINELLA LONGICEPS VAL., OFF THE COCHIN COAST - Balan, V (Indian Journal of Fisheries, 2011)
The oil-sardine catches at Cochin showed wide-fluctuations during the years of thisstudy. Relatively higher catches were obtained in 1960-61, 1966-67 and 1967-68, thehighest bsing in the 1964-65 season. Poor fishery was recorded during the seasons 1959-60,1962-63 and 1963-64. The highest catch per gear for 'thangu vala' (boat seine) was madein 1964-65. Studies on length frequency distribution indicated that the juvenile fish grewvery fast during the first 12 months. The fishery was supported largely by the dominantO-year and 1-year classes; the 2-year and 3-year old ones were less abundant. Duringeach year, commencing from 1959-60 through 1968-69, the bulk of the sardine catch wascontributedbythel35,140,125, 45,100, 130, 150, 135,130 and 115 mm modal lengthsrespectively. Ova diameter studies revealed a short period of spawning, ova beingreleased in a single batch. The peak season of spawning extends from June to August.